MULTIDISCIPLINARY APPROACH TO THE DIAGNOSIS AND TREATMENT OF INFECTIOUS COMPLICATIONS OF DIABETIC FOOT SYNDROME - Vladimir A. Beloborodov; Alexander P. Frolov (Байкальский медицинский журнал, 2024)
Introduction. Diabetic foot syndrome is one of the severe complications of diabetes mellitus. This combination of pathological processes occurring in the foot is induced and aggravated by diabetes mellitus. Most often, diabetic foot syndrome is a consequence of angiopathy, neuropathy, osteopathy; it may be accompanied by infectious and ulcera-tive lesions, leading to amputation of the extremity.The aim of the study. To assess the results of diagnosis and treatment of diabetic foot syndrome, following the intro-duction of a multidisciplinary approach.Materials and methods. A retrospective analysis of 151 medical records of patients diagnosed with diabetic foot syndrome was carried out. There were 87 (57.6 %) men and 64 (42.4 %) women; the mean age was 63.6 ± 1.0 years. The most of patients (139 (92.1 %)) were diagnosed with type 2 diabetes mellitus.Results. A multidisciplinary approach to the diagnosis and treatment of diabetic foot syndrome was achieved through the efforts of a team of specialists consisting of a surgeon, general practitioner, endocrinologist and vascular surgeon. The average glycemic level in the examined patients was higher than normal and amounted to 10.6 ± 0.4 mmol/l. In 111 of patients, the correction of carbohydrate metabolism was carried out with insulin, in the remaining observations – with tableted hypoglycemic drugs. All patients received treatment aimed at eliminating the main links in the pathogenesis of diabetic foot syndrome. Local conservative treatment was carried out in 66 cases, surgical treatment – in 85 cases. The majority of surgical interventions (40–47 %) were minor surgeries (preserving the supporting function of the leg), in 20 (23.5 %) patients surgeries were performed on the arteries, in 19 (22.4%) – high amputations (above the ankle joint), in 6 (7.1 %) – opening of foot phlegmon. The average duration of treatment for diabetic patients with diabetic foot syndrome was 17.1 ± 0.6 days.Conclusion. Patients with diabetic foot syndrome were diagnosed with severe disorders of carbohydrate metabolism with the presence of angiopathy and neuropathy. A multidisciplinary approach to the diagnosis and treatment of diabetic foot syndrome makes it possible to identify the main links in pathogenesis and, based on existing protocols, to per-sonalize the treatment. This makes it possible to preserve the supporting function of the extremity in most patients and to reduce the number of high amputations.